Effect of group exercise therapy on improving sleep quality in patients with mild to moderate depressive disorder during the acute phase - Li Ruinan; Guo Jianjun; Liu Wenyang; Qiao Yu; Tian Lu; Jia Shengtao; Zhou Jingjing (Sichuan jingshen weisheng)
BackgroundPatients with depressive disorder commonly experience sleep disturbances. Previous studies have indicated that group exercise therapy is beneficial in alleviating depressive symptom among patients with depressive disorder. However， there is a lack of research on the impact of group exercise therapy on improving sleep quality in patients with depressive disorder.ObjectiveTo explore the impact of group exercise therapy on sleep quality in patients with acute mild-to-moderate depression during the acute phase， so as to provide references for clinically improving the sleep quality of patients with mild to moderate depressive disorder during the acute phase.MethodsFrom December 2018 to July 2021， patients with mild-to-moderate depressive disorder during the acute phase （n=40）， who met the diagnostic criteria for depressive disorder according to International Classification of Diseases， tenth edition （ICD-10） ，were recruited from the outpatient clinic of Beijing Anding Hospital， Capital Medical University. All participants underwent an 8-week moderate-intensity group exercise therapy program comprising three sessions per week， each lasting 60 minutes. Assessments were conducted at baseline and after 2， 4， 6 and 8 weeks of intervention using Visual Analogue Scale （VAS）， Hamilton Depression Scale-17 item （HAMD-17） and Pittsburgh Sleep Quality Index （PSQI）. The reduction scores at each time point relative to baseline treated as the dependent variables， time as the independent variable， baseline scores as covariates， with time as a fixed effect and baseline values as random effects. Data were analyzed using a linear mixed-effects model.ResultsThe PSQI scores of patients at baseline， 2， 4 ， 6 and 8 weeks after the intervention were （10.62±5.12）， （9.07±3.58）， （7.39±3.66）， （6.54±3.84） and （5.50±3.41）， respectively. The results of linear mixed effect model analysis showed that after 2， 4， 6 and 8 weeks of intervention， patients scored lower than baseline， with statistically significant differences observed in all cases （P<0.01）. The HAMD-17 sleep fcctor scores at baseline， 2， 4， 6 and 8 weeks were （2.25±1.56）， （2.06±1.49）， （1.36±1.27）， （1.22±1.46） and （0.97±1.34）， respectively. The results of linear mixed effects model analysis showed that the HAMD-17 sleep factor scores of 4， 6 and 8 weeks of intervention were lower than that of baseline， and the difference was statistically significant （P<0.05 or 0.01）. The VAS scores at baseline， 2， 4， 6 and 8 weeks after the intervention were （3.18±2.17）， （4.74±2.22）， （6.01±2.31）， （6.54±2.16） and （7.90±1.64）， respectively. The results of linear mixed effect model analysis showed that VAS scores of 2， 4， 6 and 8 weeks of intervention were higher than baseline，and the difference was statistically significant （P<0.01）.ConclusionGroup exercise therapy may improve sleep quality and alleviate depressive symptoms in patients with mild-to-moderate depressive disorder during the acute phase. ［Funded by National Key Research and Development Plan Project （number， 2016YFC1307200）； Beijing Municipal Hospital Scientific Research and Cultivation Plan Project （number， PX2024070）］